182k views
2 votes
3(x - 4) =5x

Solving it step by step

2 Answers

1 vote

Answer: If looking to solve for x, it would be x = -6

Step-by-step explanation: Distribute the '3' to the equation '(x-4)' and that will give you '3x-12 = 5x', from there subtract the 3x from both sides to get the '-12' by itself. the equation should now look like '-12 = 2x', then divide the whole equation by '2' resulting in '-6 = x' or 'x = -6'

Hope this helps c:

User Twistar
by
5.0k points
2 votes
Given the equation, we can solve with steps:

1. Rewrite

3(x - 4) = 5x

2. Distribute

3x - 12 = 5x

3. Subtract 3 from both sides

3x - 12 - 3x = 5x - 3x

-12 = 2x

4. Divide both sides by 2

2x / 2 = x

-12 / 2 = -6

5. Simplify

-6 = x

6. Switch variable to left side

x = -6
User Iabbott
by
4.7k points